2017
DOI: 10.1016/j.jaap.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of three types of copper clad laminates considering the influence of an iron-clay catalyst in the production of pollutants

Abstract: 12Metal recovering through decomposition in the presence of steam of different wastes has 13 been demonstrated to be an effective method. In the present work, three different types of Comparing among the behavior of the three types of laminates, the emission of brominated 27 compounds is much lower in the gasification of ROGERS, compared to FR4 and CEM3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Phenol and methylphenols were also simultaneously released during the debromination of BFRs. Other studies also found that aromatic compounds such as phenol and styrene were generated from the pyrolysis of WPCB (Evangelopoulos et al, 2015;Conesa et al, 2017;Ma and Kamo, 2018). Brominated compounds were detected from thermal decomposition of BFRs-containing products by TGA-GC/MS (Terakado et al, 2011) or pyrolysis GC/MS (Evangelopoulos et al, 2015).…”
Section: Tga-ms Analysismentioning
confidence: 93%
“…Phenol and methylphenols were also simultaneously released during the debromination of BFRs. Other studies also found that aromatic compounds such as phenol and styrene were generated from the pyrolysis of WPCB (Evangelopoulos et al, 2015;Conesa et al, 2017;Ma and Kamo, 2018). Brominated compounds were detected from thermal decomposition of BFRs-containing products by TGA-GC/MS (Terakado et al, 2011) or pyrolysis GC/MS (Evangelopoulos et al, 2015).…”
Section: Tga-ms Analysismentioning
confidence: 93%